Impacts of Marine Litter on Mediterranean Reef Systems: From Shallow to Deep Waters - Angiolillo, Michela; Fortibuoni, Tomaso (Frontiers in Marine Science, 2020)
Biogenic reefs are known worldwide to play a key role in benthic ecosystems, enhancing biodiversity and ecosystem functioning at every level, from shallow to deeper waters. Unfortunately, several stressors threaten these vulnerable systems. The widespread presence of marine litter represents one of these. The harmful effects of marine litter on several organisms are known so far. However, only in the last decade, there was increasingly scientific and public attention on the impacts on reef organisms and habitats caused by litter accumulating on the seafloor. This review aims to synthesize literature and discuss the state of current knowledge on the interactions between marine litter and reef organisms in a strongly polluted basin, the Mediterranean Sea. The multiple impacts (e.g., entanglement, ghost-fishing, coverage, etc.) of litter on reef systems, the list of species impacted, and the main litter categories were identified, and a map of the knowledge available so far on this topic was provided. Seventy-eight taxa resulted impacted by marine litter on Mediterranean reefs, and the majority belonged to the phylum Cnidaria (41%), including endangered species like the red coral (Corallium rubrum) and the madrepora coral (Madrepora oculata). Entanglement, caused mainly by abandoned, lost or otherwise discarded fishing gear (ALDFG), was the most frequent impact, playing a detrimental effect mainly on coralligenous arborescent species and cold-water corals (CWCs). The information was spatially heterogeneous, with some areas almost uncovered by scientific studies (e.g., the Aegean-Levantine Sea and the Southern Mediterranean Sea). Although many legal and policy frameworks have been established to tackle this issue (e.g., Marine Strategy Framework Directive and the Barcelona Convention), several gaps still exist concerning the assessment of the impact of marine litter on marine organisms, and in particular on reefs. There is a need for harmonized and standardized monitoring protocols for the collection of quantitative data to assess the impact of litter on reefs and animal forests. At the same time, urgent management measures limiting, for instance, the impact of ALDFG and other marine litter are needed to preserve these valuable and vulnerable marine ecosystems.